STUDY ON FORMULATION OF BACTERIAL CELLULOSE NANOFIBERS-COATED NANOLIPOSOMES CONTAINING PACLITAXEL FOR ORAL ADMINISTRATION - CAO, CUONG BA; XUAN ONG, PHONG; NGUYEN, THANH XUAN (International Journal of Applied Pharmaceutics, 2024)
Objective: The low oral bioavailability of paclitaxel (PAC) because of its limited aqueous solubility and poor intestinal permeability after being administered orally suggests the need for a sustained release system. The aim of this study is to produce and evaluate in vitro a nanoliposome system that carries paclitaxel (BCN-LIP-PAC) for oral administration. Methods: Thin-film evaporation and electrostatic deposition methods were used to obtain LIP-PAC and BCN-LIP-PAC. Particle size, polydispersity index (PDI), zeta potential, morphological analysis, entrapment efficiency percentage (EE%), and in vitro dissolution studies were used to characterize the developed systems. Results: The nano-range sizes of LIP-PAC and BCN-LIP-PAC (0.1 % BCN) were 112±4.2 nm and 154±6.4 nm, respectively, where EE % were 80.6±2.3 % and 84.6±1.7 %, respectively. BCN-LIP-PAC exhibited good stability in simulated gastrointestinal ﬂuids. The drug release experiments conducted in vitro showed that BCN-LIP-PAC had obvious sustained release behaviors when compared to LIP-PAC. Furthermore, the release rate of PAC from all LIP-PAC and BCN-LIP-PAC was higher in SIF than in SGF. Conclusion: The preparation, characterization, and evaluation of BCN-LIP-PAC (0.1 % BCN) for oral PAC delivery were all successful. In conclusion, the approach presented herein is a promising option for delivering oral sustained-release PAC.